Healthy Serum-Derived Exosomes Improve Neurological Outcomes and Protect Blood–Brain Barrier by Inhibiting Endothelial Cell Apoptosis and Reversing Autophagy-Mediated Tight Junction Protein Reduction in Rat Stroke Model - Huang, Lin-Yan; Song, Jin-Xiu; Cai, Heng; Wang, Pei-Pei; Yin, Qi-Long; Zhang, Yi-De; Chen, Jie; Li, Ming; Song, Jia-Jia; Wang, Yan-Ling; Luo, Lan; Wang, Wan; et al. (Frontiers in Cellular Neuroscience, 2022)
Blood brain barrier dysfunction (BBB) causing edema and hemorrhagic transformation is one of the pathophysiological characteristics of stroke. Protection of BBB integrity have shown great potential in improving stroke outcome. Here, we assessed the efficacy of exosomes extracted from healthy rat serum in protection against ischemic stroke in vivo and in vitro. Exosomes were isolated by gradient centrifugation and ultracentrifugation, and exosomes were characterized by transmission electron microscope (TEM) and nanoparticle tracking video microscope. Exosomes were applied to middle cerebral artery occlusion (MCAO) rats or brain microvascular endothelial cell line (bEnd.3) subjected to oxygen-glucose deprivation (OGD) injury. Serum-derived exosomes were injected intravenously into adult male rats 2 hours after transient MCAO. Infarct volume and gross cognitive function were assessed 24 hours after reperfusion. Post-stroke rats treated with serum-derived exosomes exhibited significantly reduced infarct volumes and enhanced neurological function. Apoptosis was assessed via TdT-mediated dUTP nick end labeling (TUNEL) staining and the expression of Bcl-2, Bax and cleaved caspase-3 24 hours after injury. Our data showed that serum exosomes treatment strikingly decreased TUNEL+CD31+ cells in the striatum, enhanced the ratio of Bcl-2 to Bax and inhibited cleaved caspase-3 production in MCAO rats and OGD/reoxygenation insulted bEnd.3 cells. Under the consistent treatment, the expression of LC3B-II, LC3B-I and SQSTM1/p62 was detected by western blotting. Autolysosomes were observed via TEM. We found that serum exosomes reversed the ratio of LC3B-II to LC-3I, prevented SQSTM1/p62 degradation, autolysosome formation and autophagic flux. Together, these results indicated that exosomes isolated from healthy serum provided neuroprotection against experimental stroke partially via inhibition of endothelial cell apoptosis, and autophagy-mediated BBB breakdown. Intravenous serum-derived exosome treatment may therefore provide a novel clinical therapeutic strategy for ischemic stroke.